Development of the Tourist Health Resort Branch in Primorsko-Akhtarsky District - Zelinskaya, Maria V.; Chueva, Tatiana I.; Chuev, Ivan N. (International Review of Management and Marketing, 2016)
The paper studies the condition of the tourist health resort branch in one of the regions of Krasnodar Krai - Primorsko-Akhtarsky District that is characterized by the uniqueness of natural resources and significant recreational potential. The District has development prospects of environmentally friendly resorts, fishing and hunting, the creation of health complexes. Having analysed the condition, the efficiency of functioning of the tourist health resort complex, having revealed natural and resource potential and the problems of the tourist health resort sphere management in Primorsko-Akhtarsk municipality the paper offers the Increasing Management Efficiency And Quality of Services of the Tourist Health Resort Sphere of the District Project which includes: the optimization of information support of municipal tourist product merchandising at the Russian and international markets, the introduction of new excursion routes, the creation of the health complex. Keywords: tourism, high-quality recreation, increasing efficiency JEL Classifications: D61, L83